Data-driven analysis of chemicals, proteins and pathways associated with peanut allergy: from molecular networking to biological interpretation - Emmanuel Kemmler; Julian Braun; Florent Fauchère; Sabine Dölle-Bierke; Kirsten Beyer; Robert Preissner; Margitta Worm; Priyanka Banerjee (Food Science and Human Wellness)
Peanut allergy is majorly related to severe food induced allergic reactions. Several food including cow’s milk, hen’s eggs, soy, wheat, peanuts, tree nuts (walnuts, hazelnuts, almonds, cashews, pecans and pistachios), f ish and shellf ish are responsible for more than 90% of food allergies. Here, we provide promising insights using a large-scale data-driven analysis, comparing the mechanistic feature and biological relevance of different ingredients presents in peanuts, tree nuts (walnuts, almonds, cashews, pecans and pistachios) and soybean.Additionally, we have analysed the chemical compositions of peanuts in different processed form raw, boiled and dry-roasted. Using the data-driven approach we are able to generate new hypotheses to explain why nuclear receptors like the peroxisome proliferator-activated receptors (PPARs) and its isoform and their interaction with dietary lipids may have signif icant effect on allergic response. The results obtained from this study will direct future experimental and clinical studies to understand the role of dietary lipids and PPAR-isoforms to exert pro-inflammatory or anti-inflammatory functions on cells of the innate immunity and influence antigen presentation to the cells of the adaptive immunity.